Hubungan Komunikasi Interpersonal Perawat Terhadap Kepatuhan Minum Obat Pasien Diabetes Melitus Tipe 2 - Datak, Gad; Febriani, Irene (Poltekkes Kemenkes Pangkalpinang, 2020)
Compliance with drug use is an effort to achieve therapeutic success, adherence to the use of antidiabetic drugs is important because if not achieved will lead to therapy failure, which can cause complications. One strategy to increase obedience is to improve communication between doctors and nurses and patients to foster and improve interpersonal relationships. To find out the relationship between nurses' interpersonal communication and medication adherence for patients with type 2 diabetes mellitus at Pahandut Palangka Raya Health Center. This research is quantitative research. The study population was all 103 patients with type 2 diabetes mellitus. Using a purposive sampling technique of 52 respondents. This research was conducted from April to May 2019. There was a relationship between nurses' interpersonal communication and medication adherence in patients with type 2 diabetes mellitus at Pahandut Palangka Raya Health Center with a P-value = 0,000 (